Pengaruh Struktur Kepemilikan Keluarga dan Kinerja Perusahaan pada Sektor Pertambangan - Vincent Valentino; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Research on the influence of family ownership (FMO) on company performance is still little studied. This study aims to determine and prove the influence between the disclosure of family ownership and firm performance measured using return on assets. The disclosure offamily ownership is measured using a dummy variable that uses the criteria of family members occupying the Board of Director or managerial part or percentage of share ownership of 10% or more. Company performance is measured using return on assets. This research also use control variable that is good corporate governance, intensity of competition, corporate risk. This research is conducted on public company in Indonesia which has complete data in 2010-2015 and listed in Indonesia Stock Exchange (IDX) with sample size 150 observation. The results showed a significant negative relationship between family ownership and company performance. Variable of good corporate governance have negative effect to company performance, intensity of competition have a significant negative effect to companyperformance, company risk negatively significant to company performance.